Application of the Microclamped Fiber Bragg Grating (FBG) Sensor in Rock Bolt Support Quality Monitoring - Xinxin Guo; Bo Wang; Zhenyu Wang; Wei Yu; Zhenwang Ma; Tielun Yang (Advances in Civil Engineering)
The force-measuring rock bolt instrumented with bare fiber Bragg grating (FBG) sensors are generally factory-fabricated. To enable users to fabricate a force-measuring rock bolt by themselves, the microclamped FBG sensor is proposed to replace the encapsulated bare FBG sensor. A theoretical formula of strain sensitivity is also established. The strain sensibility measured by indoor calibration is consistent with the theoretical one, indicating that the microclamped FBG sensor can measure strain accurately. Besides, the measured strain sensibility coefficient (wavelength difference/strain) matches the theoretical values, making the installed microclamped sensor free from the need for recalibration and proving the installation method to be reliable. Also, the test sensitivity can be adjusted as needed. The instrumented rock bolt with microclamped FBG sensors shows great mechanical performance in the field test, awaiting further usage in applications.